• Matéria: Matemática
  • Autor: meloevandro24
  • Perguntado 5 anos atrás

20-(16+17)-[15-(18-23)]​

Respostas

respondido por: guaraciferreiraap
13

Resposta:

Explicação passo-a-passo:

Solução:

20 - (16 + 17) - [15 - (18 - 23)] =

20 - (33) - [15 - (-5)] =

20 - 33 - [15 + 5] =

20 - 33 - [20] =

20 - 33 - 20 =

-13 - 20 = -33

respondido por: sophiagatinho
7

Resposta:

Explicação passo-a-passo:

20 - (16 + 17) - [15 - (18 - 23)] =

20 - (33) - [15 - (-5)] =

20 - 33 - [15 + 5] =

20 - 33 - [20] =

20 - 33 - 20 =

-13 - 20 = -33

Perguntas similares